Respostas

2013-08-16T01:08:43-03:00
-x²+6x-5=0
∆ = b² - 4.a.c
∆ = 6² - 4.(-1).(-5)
∆ = 36 - 20
∆ = 16

x = (- b
± √∆) / 2.a
x = (-6 ± √16) / 2.(-1)
x = (-6 ± 4) / -2

x' = (-6+4) / -2
x' = -2 / -2
x' = 1

x'' = (-6-4) / -2
x'' = -10 / -2
x'' = -5

S = {1 , -5}








2013-08-16T01:45:49-03:00
-x²+6x-5=0
∆ = b² - 4.a.c
∆ = 6² - 4.(-1).(-5)
∆ = 36 - 20
∆ = 16

x = (- b 
± √∆) / 2.a
x = (-6 ± √16) / 2.(-1)
x = (-6 ± 4) / -2

x' = (-6+4) / -2
x' = -2 / -2
x' = 1

x'' = (-6-4) / -2
x'' = -10 / -2
x'' = -5

S = {1 , -5}